The effects of education and experience on youth employee wages: the case of Turkey - ÇAĞLAYAN AKAY, EBRU (My University, 2022)
Copyright © 2022 Inderscience Enterprises Ltd.The aim of this study is to reduce the disadvantages experienced by young Turkish employees, such as age discrimination, by analysing their wage structure and the factors that could affect their earnings. This study could fill the gaps in the literature on youth employee wages in the Turkish labour force. Using the 2018 Household Budget Survey data, this study addresses five research questions by estimating the extended Mincer wage equation with robust estimators to respond to the research questions. The findings show that postgraduate and bachelor’s degrees have a high incremental effect on wages and the wage gaps between the degrees are wide. Each added year of experience impacts wages because employers prefer more experienced employees to avoid the cost of training them. Young female employees earn less than young male employees because of occupational segregation, motherhood penalty, and gender norms. Due to the lack of opportunities for part-time jobs in the Turkish labour force, there is a wide gap between the wages for full-time and part-time jobs. This study contributes to a better understanding of young employees’ wage structure with robust-to-outliers econometric analysis and may guide to develop techniques to reduce the disadvantages for young Turkish individuals in the labour market.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Bilgisayar Bilimleri; Mühendislik ve Teknoloji; Social Sciences and Humanities; Economics; Computer Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Ekonomi ve İş; EKONOMİ; Engineering, Computing & Technology (ENG); Social Sciences (SOC); COMPUTER SCIENCE; ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Sosyal Bilimler ve Beşeri Bilimler; Bilgisayar Bilimi Uygulamaları; Fizik Bilimleri; Economics and Econometrics; Social Sciences & Humanities; Computer Science Applications; Physical Sciences; Mincer; MM; Robust regression; S; Turkey; Wage equation; Youth labour market